2012
DOI: 10.1371/journal.pone.0044142
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Irradiation-Dependent Fluorescence Enhancement of Hemoglobin Catalyzed by Reactive Oxygen Species

Abstract: Ultraviolet (UV) light has a potent effect on biological organisms. Hemoglobin, an oxygen-transport protein, plays an irreplaceable role in sustaining life of all vertebrates. In this study we scrutinize the effects of ultraviolet irradiation (UVI) as well as visible irradiation on the fluorescence characteristics of bovine hemoglobin (BHb) in vitro. Data show that UVI results in fluorescence enhancement of BHb in a dose-dependant manner. Furthermore, UVI-induced fluorescence enhancement is significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…6). By comparing the spectra of the first and last acquisitions, it is evident that the spectrum is evolving from that of oxy-Hb to a spectrum that represents the spectral features of methemoglobin [58], confirming that the Fe 2+ (ferrous) ion in the heme groups are changing to Fe 3+ (ferric) under UV illumination due to its high oxidation potency [61][62][63][64]. Such temporal dynamics were not observed in any of the other molecules tested in this study.…”
Section: Theory and Data Analysismentioning
confidence: 99%
“…6). By comparing the spectra of the first and last acquisitions, it is evident that the spectrum is evolving from that of oxy-Hb to a spectrum that represents the spectral features of methemoglobin [58], confirming that the Fe 2+ (ferrous) ion in the heme groups are changing to Fe 3+ (ferric) under UV illumination due to its high oxidation potency [61][62][63][64]. Such temporal dynamics were not observed in any of the other molecules tested in this study.…”
Section: Theory and Data Analysismentioning
confidence: 99%
“…It is known that at least two factors should contribute to the periodical changes. Second, our previous results 37 , 40 and other researchers’ work 41 demonstrated that UVA light could lead to hemoglobin decomposition rather than cross-linking. Meanwhile, as the important effector of UV irradiation, ROS was found to degrade hemoglobin.…”
Section: Discussionmentioning
confidence: 77%
“…PKA activity in intact erythrocytes was assessed by using confocal microscopy. Since UV illumination ( % 360 nm) is known to have an immediate untoward impact on hemoglobin biochemistry, [19] we employed a 405 nm laser to convert the DNMB-peptide 3 to its phosphorylatable counterpart. Upon photolysis, a rapid fluorescence response is observed in the interior of erythrocytes (Figure 3 and Figures S22-S25).…”
Section: Methodsmentioning
confidence: 99%